Intergenerational transmission of socioeconomic conditions in Austria in the context of European welfare regimes - Schnetzer, Matthias; Altzinger, Wilfried (Momentum Quarterly, 2013)
This paper uses data from the European Union Statistics on Income and Living Conditions (EU-SILC) 2005 to analyze intergenerational income mobility in Austria compared to other European Union members. Applying various methodological approaches, the data reveal substantial differences in intergenerational income persistence across European welfare regimes. The results show that income class rigidities are much less evident in Nordic countries compared to other European countries including Austria.